2013
DOI: 10.5039/agraria.v8i2a2409
|View full text |Cite
|
Sign up to set email alerts
|

Metodologia dos modelos mistos para seleção combinada em progênies segregantes de mamoeiro

Abstract: RESUMOApesar de o Brasil se destacar como um dos principais produtores mundiais de mamão, ainda existe um reduzido número de linhagens/híbridos disponíveis para comercialização. O presente trabalho objetivou selecionar linhagens entre e dentro de progênies em uma população segregante de mamoeiro para avanço das autofecundações. Originalmente a população foi desenvolvida via retrocruzamento objetivando a incorporação (característica Golden) para tolerância à mancha fisiológica nos genitores do híbrido UENF/CALI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
25
2
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 22 publications
4
25
2
4
Order By: Relevance
“…The mean value of SS contents was 13.66 °Brix, TA was 0.098% citric acid, and the SS/TA ratio was 145.99 (Table 2). These values agree with those obtained by Pinto et al (2013a) and Reis et al (2015), except for fruit weight, which was lower in the present study, but compatible with that of traditional Solo cultivars (Oliveira & Vitória, 2011;Costa et al, 2013). For the genotypes of the Formosa group, the mean number of fruits was 16.12, each weighing 1,298.82 g, and plant production per plant was of 20.37 kg.…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…The mean value of SS contents was 13.66 °Brix, TA was 0.098% citric acid, and the SS/TA ratio was 145.99 (Table 2). These values agree with those obtained by Pinto et al (2013a) and Reis et al (2015), except for fruit weight, which was lower in the present study, but compatible with that of traditional Solo cultivars (Oliveira & Vitória, 2011;Costa et al, 2013). For the genotypes of the Formosa group, the mean number of fruits was 16.12, each weighing 1,298.82 g, and plant production per plant was of 20.37 kg.…”
Section: Resultssupporting
confidence: 82%
“…The Golden cultivar was grouped with the genotypes with lower PP and FW in the two harvest seasons. This reinforces the results obtained by Pinto et al (2013aPinto et al ( , 2013b, who observed the degeneration of the Golden cultivar due to the indiscriminate production of seeds, which causes the loss of its original characteristics.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations